Penegakan Hukum Terhadap Tindak Pidana Pemerasan Dan Pengancaman Di Medan (Studi Putusan Nomor 2731/Pid.B/2022/PN.Mdn) - Manurung, Daniel; Lubis, Anggreni Atmei (JUNCTO: Jurnal Ilmiah Hukum, 2024)
The purpose of this study is to analyze criminal liability for perpetrators of extortion and intimidation crimes and to analyze judges' considerations for extortion and intimidation crimes in Medan City in decision No. 2731/Pid.B/2022/PN.Mdn. This normative juridical research analyzes legal norms and their application in the crime of extortion based on Article 368 of the Criminal Code and Decision No. 2731/Pid.B/2022/PN.Mdn. Data was collected through literature studies and interviews, and qualitative analysis with an inductive mindset to evaluate the effectiveness of law enforcement and judges' considerations in the case. The results of the study show that the criminal liability of extortion perpetrators is regulated in Article 368 of the Criminal Code with a maximum penalty of 9 years in prison, which can be aggravated according to Article 368 paragraph (2) of the Criminal Code. In case No. 2731/Pid.B/2022/PN.Mdn, the judge ruled that all elements in Article 368 paragraph (1) jo Article 55 paragraph (1) 1 of the Criminal Code were fulfilled, without justification or excuse. After considering the aggravating and mitigating factors, each defendant was sentenced to 3 years in prison.